Caesarean Section, Vaginal Delivery and Post Natal Depression - MH Baghianimoghadam; D Shodjaee zadeh; AH Aminian (Tehran University of Medical Sciences, 2009)
Background: Depression is a kind of sorrow that decreases the level of juiciness. Most studies have maintained that psychological risk factors have the most profound effect on the development of postnatal depression (PND). We compared the postnatal depression among the women with elective caesarean and vaginal delivery.  Methods: This cross- sectional study was carried out on 120 women 1-4 months after their delivery. Samples were divided in two groups (60 mothers with caesarean and 60 with vaginal delivery).The samples were selected by cluster sampling in Health Center of Yazd City, Yazd Province. To assess the level of depression, we handed the Beck De-pression Inventory (BDI) to participants. For data analysis, qui- square, ANOVA and descriptive statistic were used. Results: The mean grade scores of depression of women with caesarean delivery was 17.16 (SD=11.57) and for women with vaginal delivery was 11.05 (SD=9.41).The major depression in women with caesarean was twice the women with vaginal delivery (16.7 via 8.3). There was significant difference between mode of delivery and depression of participants (P=0.02).Tendency of sexuality in women with caesarean was lower than women with vaginal delivery. Conclusion: Although the prevalence of PND symptoms seems to be the same across the cultures, risk factors differ significantly. This study identified caesarean delivery as a certain risk factor for increasing prevalence of depression in postnatal delivery. This factor must be taken into consideration when planning intervention and preventive strategies for these women.